An event generator for neutrino-induced deep inelastic scattering and applications to neutrino astronomy - Silvia Ferrario Ravasio; Rhorry Gauld; Barbara Jäger; Alexander Karlberg; Giulia Zanderighi (European Physical Journal C: Particles and Fields)
Abstract We extend the recently presented, fully exclusive, next-to-leading-order accurate event generator for the simulation of massless neutral- and charged-current deep inelastic scattering (DIS) to the case of incoming neutrinos. The generator can be used to study neutrino-nucleon interactions at (ultra) high energies, and is relevant for a range of fixed-target collider experiments and large-volume neutrino detectors, investigating atmospheric and astrophysical neutrinos. The matching with multi-purpose event generators such as PYTHIA 8 is performed with the POWHEG method, and accounts for parton showering and non-perturbative effects such as hadronization. This makes it possible to investigate higher-order perturbative corrections to realistic observables, such as the distribution of charged particles. To illustrate the capabilities of the code we provide predictions for several differential distributions in fixed-target collisions for neutrino energies up to $$1~PeV $$ 1 PeV .